2019
DOI: 10.1177/0734371x19863841
|View full text |Cite
|
Sign up to set email alerts
|

Pay-for-Performance and Other Practices: Alternative Paths for Human Resource Management Effectiveness in Public Social Care Organizations

Abstract: Pay-for-performance has been widely adopted in the public sector to improve effectiveness and efficiency in service provision, which in turn positively affects employees’ satisfaction and commitment. Despite the presence of these initiatives in nearly every reform effort, limited concrete evidence of success has been highlighted. Through a fuzzy set qualitative comparative analysis on 17 social care organizations in Italy, the aim of this work is to contribute to the debate on human resources management practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 123 publications
0
7
0
Order By: Relevance
“…Bolstered employee job satisfaction is one of the most significant outcomes resulting from SHCM utilization. Research suggests that when organizations engage in SHCM initiatives, employees are more likely to notice and appreciate the value that is assigned to their individual human capital (H. Lee, 2017;Mariani et al, 2021). By investing in employee human capital through SHCM, organizations demonstrate a firm commitment to enhancing individual growth, development, and work experiences.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Bolstered employee job satisfaction is one of the most significant outcomes resulting from SHCM utilization. Research suggests that when organizations engage in SHCM initiatives, employees are more likely to notice and appreciate the value that is assigned to their individual human capital (H. Lee, 2017;Mariani et al, 2021). By investing in employee human capital through SHCM, organizations demonstrate a firm commitment to enhancing individual growth, development, and work experiences.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Such practices include professional development, supervisory support, and employee engagement. These practices are routine in progressive organizations and validated by the literature as effective managerial strategies (Breaugh, 2021;Giauque et al, 2022;Gould-Williams, 2004;Hameduddin & Fernandez, 2019;Hassett, 2022;Jakobsen et al, 2019;Johansen & Sowa, 2019;Mariani et al, 2021;McGregor, 1991;Park et al, 2018;Penning de Vries et al, 2022;Selden, 2009;Walk et al, 2022). In short, this research is explicitly interested in testing a causal model that explores the effects of the aforementioned SHCM practices on job satisfaction, as well as the endogenous relationship between job satisfaction and employee turnover intention.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, public HRM studies have suggested that the alignment among managerial treatments at the same management levels can increase the positive outcomes for employees, whereas unaligned treatments can reduce the effects. For instance, at high levels of management, Mariani et al (2019) reported that pay-for-performance can positively interact with other empowering practices to affect public employees, whereas Borst et al (2019) found that red tape negatively interacts with organization-related resources to foster public employees’ work engagement. At lower levels of management, Shim et al (2019) showed that work overload negatively interacts with supervisor support, job-goal specificity, and performance feedback to influence public employee OCB.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Employees went on strike and many German customers boycotted Amazon (Huffington Post, 2013; The Wall Street Journal, 2014). Not only have multinational organisations experienced difficulties implementing merit pay systems across cultures but national governments experience similar problems (Bae, 2021; Bryson et al., 2017; Mariani et al., 2021). Governments in Asian countries have tried to introduce a merit pay system for public employees to replace traditional seniority‐based systems.…”
Section: Introductionmentioning
confidence: 99%